Vascular and autonomic function as early predictive biomarkers of the progression to gestational hypertension - Claudio Joo Turoni; Silvia Benvenuto; Rodrigo O. Marañón; Rossana Chahla; María Peral de Bruno (Elsevier, 2023)
Background: The changes in endothelial function, arterial stiffness, and heart rate variability (HRV) produced in the first trimester of pregnancy in women who develop gestational hypertension (GH) are still being investigated. Objective: to evaluate the HVR, endothelial function, and arterial stiffness changes during the first trimester of pregnancy and their relationship with the development of GH Methods: A group of women normotensive during the first trimester (n = 43), who later did (GH; n = 11) or did not (no-GH; n = 32) develop GH in that pregnancy, were enrolled. In the first trimester, endothelial function and arterial stiffness were evaluated through photoplethysmography. HRV, parasympathetic (PNS), and sympathetic (SNS) indexes were measured in a 5-minute continuous electrocardiogram record at rest sitting. The Griess reaction measured urinary nitrite excretion (NOx). Results: Systolic blood pressure (SBP) values were higher in GH (no-GH: 105.8 ± 2.0 vs. GH: 112.7 ± 3.0 mmHg; p < 0.05). Endothelial function was decreased, and arterial stiffness was increased in GH. Only in GH the arterial stiffness was correlated with SBP (Pearson's r: 0.5594; 95%CI: 0.06106-0.8681; p < 0.05). In HRV, GH decreased low-frequency power and the ratio SD2/SD1. The inhibition of PNS was lower in GH. The NOx was reduced in GH (no-GH: 3.4 ± 0.4 vs. GH: 0.3 ± 0.1 μM/L; p < 0.001). NOx was correlated negatively with the SNS index only in GH. Conclusions: Developed GH is preceded early in pregnancy by endothelial dysfunction and increased arterial stiffness. In this context, there are SNS-PNS interrelation modifications with less inhibition of PNS.